Interpersonal relations and social patterns in communication technologies : discourse norms, language structures and cultural variables - Park, Jung-ran.; Abels, Eileen G. (Information Science Reference, 2010)
"This book provides interdisciplinary perspectives utilizing a variety of research methods to uncover the fundamental components of computer-mediated communication (i.e., language, interpersonal relations/communication and information technology) which will be discussed in the following section"--Provided by publisher.